MASE: Multi-Agent System for Environmental Simulation - Ralha, Célia G.; Abreu, Carolina G.; Coelho, Cássio G. de C. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2013)
MASE is a multi-agent system designed as a framework to characterize, predict and explore the land-use change dynamics. It aims to assist the decision-making process by the use of environmental simulations, which is based on a hybrid modeling technique. The methodological two-fold approach intends to form a solid backbone and a replicable parameterization process. The framework is illustrated with a case study of the Brazilian Cerrado using a spatially explicit model.